Introduction to Polymers - Young, Robert J.; Lovell , Peter A. (Boca : Raton CRC Press, 2011)
Introduction to Polymers, Third Edition presents the science underpinning the synthesis, characterization and properties of polymers. The material has been completely reorganized and expanded to include important new topics and provide a coherent platform for teaching and learning the fundamental aspects of contemporary polymer science.
Includes Bibliographical References; Index 653-668p.
Keywords: Polymer; Chemistry